IMPLEMENTASI PROGRAM BPJS KESEHATAN DALAM MENINGKATKAN KUALITAS PELAYANAN KESEHATAN DI KOTA TANGERANG - Effendi Effendi; M.Z. Babul Gaos (Universitas Muhammadiyah Tangerang, 2017)
This study aims to find out how the influence of the Health BPJSProgram Implementation on the quality of health services at SitanalaLeprosy Hospital Dr. The city of Tangerang, with the formulation of theproblem: Is there an effect of the implementation of the BPJS healthprogram on the Quality of Health Services at the Leprosy Hospital Dr.Sitanala Tangerang City? The number of samples of 40 techniques usedis Random Sampling from 161 populations, the primary data obtainedfrom respondents through a questionnaire. data analysis techniques withregression analysis and static tests (different tests). The results of thestatistical test showed that there was a significant effect of theImplementation of the Health BPJS Program on the quality of healthservices at the Leprosy Hospital Dr. Sitanala Tangerang